Assessment of Cd bioavailability using chemical extraction methods, DGT, and biological indicators in soils with different aging times. (June 2022) - Ma, Pan; Tian, Tian; Dai, Zhaoyi; Shao, Tingyu; Zhang, Wei; Liu, Mingda
Abstract: Total cadmium (Cd) cannot be used to accurately assess the ecological risk of Cd pollution in soil. Currently there is no universally recognized method to evaluate Cd bioavailability in soil. In this study, chemical extraction methods, diffusive gradients in thin films (DGT) and bioindicator methods were used to evaluate Cd bioavailability in soils with the same properties but different aging times. Results indicate that aging decreased the Cd bioavailability in soil and its toxicity to barley. This was primarily due to a decrease in the proportion of ion-exchangeable Cd. Correlation analyses were conducted on the Cd bioavailable content obtained via the soil extraction methods and the toxicity effect of barley. Results showed that the order of the minimum value of the linear regression determination coefficient ( R 2 ) of chemical extraction methods and DGT was as follows: DGT-Cd (0.7385, p < 0.05) > total Cd (0.6931, p < 0.05) > acetic acid-Cd (0.6078) > ion-exchangeable Cd (0.5933) > DTPA-Cd (0.5842) > CaCl2 -Cd (0.4980) > water-soluble Cd (0.4602). The order of minimum value of R 2 of biological indicators of barley was integrated biomarker response (IBR) (0.8501, p < 0.01) > length (0.6492) > dry weight (0.6320) > fresh weight (0.4980) > Cd concentration (0.4602). The root is more suitable for indicating the plant uptake and accumulation of Cd in soil. Meanwhile, the shoot can effectively evaluate the toxic effect of Cd stress on plants. DGT is more suitable to reflect Cd bioavailability to barley compared to chemical extraction methods, Furthermore, it can be used to evaluate stable polluted soil with longer aging time. In the study of the bioavailability of heavy metals in soil, IBR can be used as a reliable reference index to contribute to the comprehensive evaluation of metal bioavailability in addition to considering plant uptake. Graphical abstract: Image 1 Highlights: Soil aging decreased Cd bioavailability due to lower ion-exchangeable Cd content. IBR can well evaluate Cd bioavailability in soil. Compared to chemical extraction method, DGT method showed a higher correlation with biological indicators of barley.